Incidencia del crecimiento económico en las emisiones de CO2: un análisis comparativo (1980-2008) (2014)
Economic growth today is often a priority for most countries, economic policy objective and concern of academics around the world, and that it could theoretically reach improved well-being and quality of life of the population. However, during the process that is carried out to improve the growth levels of different activities resource exploitation and production, not to be given greater importance, for many years have led to a deterioration of the environment are developed.